COLLABORATIVE GOVERNANCE ANTARA PEMERINTAH DAN SWASTA DALAM PENGELOLAAN SAMPAH (STUDI KASUS: DESA SIDAKARYA, KOTA DENPASAR) - Rukmawati, Diah; Arti, Ida Ayu Bulan Utami (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2026)
The purpose of this study is to identify and characterize the collaborative governance approach that PT. Sangkara and the Sidakarya Village Government use, specifically when it comes to managing inorganic waste. Using a case study method, a qualitative approach was employed. Participatory observation, in-depth interviews, and literature reviews were the methods used to gather data. The research findings, which were derived from the collaborative governance analysis framework created by Ansell and Gash (2007), demonstrate that the cooperation process between PT Sangkara and the Sidakarya Village Government has met five collaboration indicators, including establishing commitments between actors, enhancing interactions and trust, and establishing dialogue mechanisms. The waste management paradigm was successfully changed from a technical disposal problem to a valuable strategic tool as a result of this cooperative effort. Furthermore, this study demonstrates that private actors' participation in waste management at the Sidakarya Village level strives to address social and political concerns as well as the community's development needs. By extending the study of collaborative governance, this study contributes to the advancement of government science by demonstrating that cooperation between the public and private sectors is not just a formal structure but is also impacted by the political and economic judgments of the village government. The results of this study can empirically demonstrate that, in the context of Bali, cooperative waste management can be used as a platform for testing out contemporary governance that is responsive to contemporary environmental issues.